ANALISIS KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN 5 SUNGAI RAYA - Khairunisa; Yunika Afryaningsih; Risdiana Andika Fatmawati (STKIP Subang, 2025)
Reading ability is a fundamental skill that is very important for elementary school students because it plays a role in cognitive, social, and emotional development. This study aims to describe the early reading abilities of second-grade students at SDN 5 Sungai Raya. The research method used a descriptive qualitative approach with data collection techniques through the EGRA (Early Grade Reading Assessment) test, which covers five aspects: letter recognition, word reading, reading meaningless words, reading fluency and reading comprehension, and listening comprehension. The results of the study show that most students still have difficulties. Of the eight research subjects, five students were unable to recognize letters randomly, four students were not fluent in reading whole words, and five students had difficulty reading meaningless words, with one student completely unable to pronounce them. In terms of reading aloud and reading comprehension, four students were not fluent and did not fully understand the text. Meanwhile, two students still had difficulties in listening to the reading. In conclusion, the early reading skills of second-grade students at SDN 5 Sungai Raya are still relatively low and require further attention. The role of teachers, varied learning strategies, supporting media, and parental support are important factors in improving students' reading skills from an early age.